2013
DOI: 10.1063/1.4809515
|View full text |Cite
|
Sign up to set email alerts
|

Faster and highly luminescent ferroelectric liquid crystal doped with ferroelectric BaTiO3 nanoparticles

Abstract: The results pertaining to faster electro-optic response time and improved photoluminescence (PL) of BaTiO3 nanoparticles (BT NPs) doped ferroelectric liquid crystal (FLC) are presented. The observed increase (∼2 fold) in PL intensity and simultaneous reduction of response time have been achieved for an optimal BT NPs doping of 0.2 wt. %. These are attributed to the large dipole moment of BT that couples effectively with that of FLC molecules. These studies would provide benchmark for realization of high lumine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…[12,14,17,[21][22][23][24][25]27,28,[31][32][33] Unfortunately, not all of the works cited above contain reliable evidence for the absence of aggregation in such composites (observation of the bulk by the naked eye is not considered as evidence). This undesirable process is often observed irrespectively of the type of the NPs [3][4][5]18,22,23,25,34] and it severely restricts careful investigations on these materials. In several works, it was mentioned that simple alkyl-aliphatic surfactants do not allow obtaining stable composites LC doped by NPs over time.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…[12,14,17,[21][22][23][24][25]27,28,[31][32][33] Unfortunately, not all of the works cited above contain reliable evidence for the absence of aggregation in such composites (observation of the bulk by the naked eye is not considered as evidence). This undesirable process is often observed irrespectively of the type of the NPs [3][4][5]18,22,23,25,34] and it severely restricts careful investigations on these materials. In several works, it was mentioned that simple alkyl-aliphatic surfactants do not allow obtaining stable composites LC doped by NPs over time.…”
Section: Introductionmentioning
confidence: 95%
“…[1][2][3][4][5] Such materials combine technological potential of LC with unique properties of NPs. Thus, NPs dispersed in LCs can improve magnetic, [6][7][8][9][10][11][12][13][14][15][16][17] electrooptic and dielectric [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] properties to the resultant material. Typically, nematic LCs are mostly used as a carrier for such composites.…”
Section: Introductionmentioning
confidence: 99%
“…The dielectric permittivity and dielectric strength was noticed to decrease with increase in the concentration of silica nanoparticle in SmC* phase and relaxation frequency and was found to increase with increase in the silica concentration and temperature in SmC* and decreases as we approach towards transition temperature. P. Ganguly et al presented the results pertaining to faster electro-optic response time and improved photoluminescence of BaTiO 3 nanoparticles doped ferroelectric LC [75]. Increase in photoluminescence intensity and simultaneous reduction of response time had been achieved for an optimal BaTiO 3 nanoparticles doping of 0.2 wt %.…”
Section: Properties Of Doped Ferroelectric Liquid Crystalsmentioning
confidence: 96%
“…Ferroelectric NPs doped LCs also have decreased voltage of the electrically driven texture transitions and the Bragg reflection in cholesteric LCs, 13 as well as changing the spontaneous polarization of the ferroelectric smectic LCs. 14,15 Furthermore, ferroelectric NPs may even induce a smectic ordering in a nematic LC. 16,17 It has been suggested that the significant effect on the liquid crystal matrix originates from the permanent polarization of the ferroelectric particles.…”
mentioning
confidence: 99%